The Association of Interleukin 6−634C/G Polymorphism With Left Atrial Thrombus and Severe Spontaneous Echocontrast in Patients With Atrial Fibrillation. (November 2013) - Deng, Xin-Tao; Jiang, Min-Hui; Zhu, Jian-Hua; Ge, Li-Jun; Guo, Jing; Gao, Shu-Ping; Zheng, Jin-Guo; Luan, Hong; Shi, Gui-Liang; Wang, Ru-Xing; Shi, Hai-Feng; Pan, Min
Atrial fibrillation (AF) not only is an independent risk factor for death but also confers significant risk of morbidity from stroke associated with left atrial thrombus. The association of interleukin 6 ( IL-6 ) polymorphism with thrombus in AF has not been investigated before. We carried out a case–control study in Han Chinese. The IL-6 −634C/G genotypes of 31 patients with thrombus and 45 patients without thrombus were detected by polymerase chain reaction and restriction fragment length polymorphism. The frequencies of the IL-6 genotypes (CC, CG, and GG) were 29.03%, 54.54%, and 16.13% for the patients with thrombus, and 55.56%, 40.00%, and 4.44% for the patients without thrombus, respectively ( P = .0391). Compared with the CC genotype, the G allele carriers (CG + GG) had a 2.79-fold increased risk of thrombus or severe spontaneous echocontrast (SEC). These results suggest that IL-6 −634C/G polymorphism is associated with thrombus and severe SEC, and the G allele is an independent risk for thrombus and severe SEC in Han Chinese patients with AF.